Establishment of an in vitro culture system, based on small intestinal crypt organoids, for the investigation of putative small intestinal stem cells - Gulino, Maria E. (2016)
Small intestinal (SI) stem cells differentiate into short-lived progeny, except lysozyme-expressing Paneth cells. In vivo, the Tet-Op histone 2 B (H2B) - green fluorescent protein (GFP) fusion protein transgenic mouse has been employed to analyse the slow-cycling putative small intestinal epithelial stem cells, at cell position +4 (cp4 cells), through doxycycline-inducible transient expression of H2B-GFP. The aim of the study was to employ the same genetic mouse model in order to develop a culture system in which was possible to detect and investigate H2B-GFP-retaining putative SI stem cells. SI crypts isolated from 6-12 weeks old Tet-Op-H2B-GFP transgenic mice were established in culture (designated organoids) using growth factors and Matrigel. For in vitro transgene expression, doxycycline was added to the complete culture medium for 24/48 hours (pulse). H2B-GFP and lysozyme expression was studied by confocal and fluorescence microscopy. Percentages of H2B-GFP-retaining putative SI stem cells and of H2B-GFP-retaining Paneth cells persisting in organoids were determined by scoring GFP-immunoreactive cells. Ulex europaeus-I lectin (UEA-I) cell labelling, combined with flow cytometry, was employed in a pilot study aimed at establishing a protocol for the separation of H2B-GFP-retaining putative SI stem cells from H2B-GFP-retaining Paneth cells persisting in the small intestine of chased mice.